2019
DOI: 10.1109/access.2018.2881020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Research of Swarm Intelligence Clustering Algorithms for Analyzing Medical Data

Abstract: As the Internet of medical Things emerge in the field of medicine, the volume of medical data is expanding rapidly and along with its variety. As such, clustering is an important procedure to mine the vast data. Many swarm intelligence clustering algorithms, such as the particle swarm optimization (PSO), firefly, cuckoo, and bat, have been designed, which can be parallelized to the benefit of mass data computation. However, few studies focus on the systematic analysis of the time complexities, the effect of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The SI algorithms FFA, CS, BA, and PSO were compared in medical data clustering and results revealed that CS performs slower than others and PSO and BA are relatively faster than others [ 17 ]. Figueiredo et al [ 18 ] studied the comparison of SI algorithms in the clustering domain and concluded that PSO is the best performing algorithm.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The SI algorithms FFA, CS, BA, and PSO were compared in medical data clustering and results revealed that CS performs slower than others and PSO and BA are relatively faster than others [ 17 ]. Figueiredo et al [ 18 ] studied the comparison of SI algorithms in the clustering domain and concluded that PSO is the best performing algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…In this study, we focused on comparing the standard SI algorithms. We adopted and used the default parameters of SI algorithms that were introduced in the literature experiments for generic optimization, with different examples [ 17 , 42 ]. Although our experimental problem was text document clustering, which is not an optimization problem, we applied the initial parameter settings of the optimization problem case to ours and tested those standard SI algorithms.…”
Section: Algorithms For Text Document Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…In the above article [1], Zhihua Liu was erroneously omitted as the corresponding author. It should be noted that he should be considered the corresponding author for this article.…”
mentioning
confidence: 99%